The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1093/ajcn/87.6.1852
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate infant feeding practices result in better growth of infants and young children in rural Bangladesh

Abstract: Our results provide strong evidence for the positive effects of following the current infant feeding recommendations on growth of infants and young children. Intervention programs should strive to improve conditions for enhancing current infant feeding recommendations, particularly in low-income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
178
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(191 citation statements)
references
References 37 publications
8
178
2
3
Order By: Relevance
“…One longitudinal study in Bangladesh constructed an infant feeding scale and found that children who scored higher on the infant feeding scale were more likely to have better growth later in infancy. Although that study was able to capture many of the core infant feeding practices outlined by the WHO in their scale, the relationship between food variety and child growth could not be evaluated due to lack of adequate data on foods fed to children (16) .While these studies have used composite infant feeding scales and indices that captured many of the WHO-recommended IYCF practices, many other studies have focused only on the relationship between specific aspects of IYCF and child growth. For example, the association between breast-feeding practices and child growth has been investigated in a number of settings: Bangladesh (17,18) , Malawi (19) , Brazil (20,21) , Columbia (22) , Turkey (23) , rural Senegal (24) and Mexico (25,26) .…”
mentioning
confidence: 99%
“…One longitudinal study in Bangladesh constructed an infant feeding scale and found that children who scored higher on the infant feeding scale were more likely to have better growth later in infancy. Although that study was able to capture many of the core infant feeding practices outlined by the WHO in their scale, the relationship between food variety and child growth could not be evaluated due to lack of adequate data on foods fed to children (16) .While these studies have used composite infant feeding scales and indices that captured many of the WHO-recommended IYCF practices, many other studies have focused only on the relationship between specific aspects of IYCF and child growth. For example, the association between breast-feeding practices and child growth has been investigated in a number of settings: Bangladesh (17,18) , Malawi (19) , Brazil (20,21) , Columbia (22) , Turkey (23) , rural Senegal (24) and Mexico (25,26) .…”
mentioning
confidence: 99%
“…The WHO and United Nations Children Fund have articulated a global strategy for infant-and young child-feeding. Optimal infant-and young child-feeding (IYCF) practices are crucial for nutritional status, growth, development, health, and ultimately the survival of infants and young children [3][4][5] . Worldwide, suboptimal breastfeeding still accounts for deaths of 1.4 million children aged less than five years (under-five mortality).…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that, if 90% of infants are covered with a package of intervention to protect, promote, and support the optimal IYCF practices, almost one-fifth of overall under-five mortality can be averted 6 . The poor complementary feeding practices mean that many children continue to be vulnerable to irreversible outcomes of stunting, poor cognitive development, and significantly increased risk of infectious diseases, such as diarrhoea and acute respiratory infection 5,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Scientific evidence indicates that inappropriate feeding practices can have profound consequences for the growth, development and survival of infants and children. Various in appropriate complementary feeding practices such as; untimely introduction of complementary food, improper feeding frequency and low dietary diversity of complementary foods have been shown to have numerous negative effects on children's health [1,[6][7][8]. Appropriate complementary feeding entails; introduction of complementary foods at 6 months with continued breastfeeding up to at least 2 years and beyond, correct feeding frequency for age and consumption of adverse diet [9].…”
Section: Introductionmentioning
confidence: 99%